Validation of the Slow Off‐Kinetics of Sirtuin‐Rearranging Ligands (SirReals) by Means of Label‐Free Electrically Switchable Nanolever Technology. (22nd January 2020) - Schiedel, Matthias; Daub, Herwin; Itzen, Aymelt; Jung, Manfred
Abstract: We have discovered the sirtuin‐rearranging ligands (SirReals) to be highly potent and selective inhibitors of the NAD + ‐dependent lysine deacetylase Sirt2. Using a biotinylated SirReal in combination with biolayer interferometry, we previously observed a slow dissociation rate of the inhibitor–enzyme complex; this had been postulated to be the key to the high affinity and selectivity of SirReals. However, to attach biotin to the SirReal core, we introduced a triazole as a linking moiety; this was shown by X‐ray co‐crystallography to interact with Arg97 of the cofactor binding loop. Herein, we aim to elucidate whether the observed long residence time of the SirReals is induced mainly by triazole incorporation or is an inherent characteristic of the SirReal inhibitor core. We used the novel label‐free switchSENSE® technology, which is based on electrically switchable DNA nanolevers, to prove that the long residence time of the SirReals is indeed caused by the core scaffold. Abstract : Take your time choosing : Using the novel label‐free switchSENSE ® technology, we were able to validate the long residence time of the sirtuin‐rearranging ligands (SirReals) selectively binding to Sirt2. We found that a long residence time as a consequence of an induced‐fit mechanism can be an important driver of pharmacological selectivity.